Penerapan Model Pendidikan Multikultural dalam Meningkatkan Toleransi dan Kesadaran Siswa di Sekolah - Ramadhan, Maratu Naja; Albina, Meyniar (TSAQOFAH, 2025)
Multicultural education is a crucial component in creating an inclusive learning environment in Indonesia, a nation renowned for its cultural diversity. This study aims to identify multicultural education models implemented in schools, supporting factors, and obstacles in their implementation. The research employs a qualitative method with a library research approach, gathering data from various books and journal sources. The findings reveal that multicultural education models include curriculum revision, reforming learning systems, and integrating multicultural values into school activities. Supporting factors for success include a positive school climate, an inclusive curriculum, and active roles of teachers. Conversely, challenges faced include ineffective communication among students, a lack of educational media, and limited socialization outside the classroom. This study concludes that by addressing these barriers, multicultural education can make a more significant contribution to building a tolerant and respectful society.